Development of an Experimental Method Using a Portable Photosynthesis-Monitoring System to Measure Respiration Rates in Small-Sized Insects - Bi-Yue Ding; Qin-Qin Xu; Yu-Jing Liu; Yu-Hong Zhong; Yan Zhou (Insects)
Respiration rates in insects are critical for survival and environmental adaptation, being influenced by developmental stages, environmental conditions, and the regulation of mitochondrial protein-coding genes. However, methods for field-based measurements in small-sized insects remain limited. In this study, we established a portable photosynthesis system to quantify respiration rates in five small-sized insects (body length < 8 mm): Acyrthosiphon pisum, Aphis citricidus, Tuta absoluta, Tribolium castaneum, and Bactrocera dorsalis. We tested its effectiveness across life stages and under diverse treatments, including light/dark cycles, insecticides, temperature shifts, starvation, mitochondrial inhibitors, and RNA interference. The system exhibited high sensitivity and reproducibility rates, revealing stage-specific respiration patterns. Various treatments, as well as expression changes in mitochondrial protein-coding genes, significantly affected respiration rates. This study validates the portable system as a reliable tool for insect respiration studies and highlights regulatory networks associated with respiratory plasticity. These findings enhance experimental methodologies and advance our understanding of insect adaptation to environmental stressors and pest control strategies.